2016
DOI: 10.1089/ten.tea.2015.0313
|View full text |Cite
|
Sign up to set email alerts
|

Decellularized Liver Extracellular Matrix as Promising Tools for Transplantable Bioengineered Liver Promotes Hepatic Lineage Commitments of Induced Pluripotent Stem Cells

Abstract: Liver transplantation is the last resort for liver failure patients. However, due to the shortage of donor organs, bioengineered liver generated from decellularized whole liver scaffolds and induced pluripotent stem cell (iPSC)-derived hepatocytes (iPSC-Heps) is being studied as an alternative approach to treat liver disease. Nevertheless, there has been no report on both the interaction of iPSC-Heps with a liver extracellular matrix (ECM) and the analysis of recellularized iPSC-Heps into the whole liver scaff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
109
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(111 citation statements)
references
References 55 publications
2
109
0
Order By: Relevance
“…Gel electrophoresis of UBM hydrogels shows similar bands to SIS hydrogels and both show additional bands corresponding to other ECM proteins [20]. Intact growth factors have also been confirmed in adipose [50], colon [51], liver [52], and SIS [53] ECM hydrogels, although present in reduced amounts compared to native tissue or ECM scaffolds. The impact of solubilization on cryptic peptide and matrix-bound nanovesicle content or activity has yet to be evaluated.…”
Section: Ecm Hydrogel Characterizationmentioning
confidence: 99%
“…Gel electrophoresis of UBM hydrogels shows similar bands to SIS hydrogels and both show additional bands corresponding to other ECM proteins [20]. Intact growth factors have also been confirmed in adipose [50], colon [51], liver [52], and SIS [53] ECM hydrogels, although present in reduced amounts compared to native tissue or ECM scaffolds. The impact of solubilization on cryptic peptide and matrix-bound nanovesicle content or activity has yet to be evaluated.…”
Section: Ecm Hydrogel Characterizationmentioning
confidence: 99%
“…Due to the unlimited selfrenewing capacity and less immunogenicity of iPSCs, they became a preferred choice for hepatocyte generation. 13 In this present study, we hypothesize that the decellularized WP scaffold (DWJS) prepared in vitro may be an ideal scaffold for cultivating and differentiating iPSCs to hepatocytes. 28,29 However, there is only one report describing the use of hiPSCs-derived hepatocytes (hiPSC-Heps) to repopulate decellularized scaffolds.…”
mentioning
confidence: 90%
“…In the case of liver, primary hepatocytes are mainly used to reseed decellularized liver scaffolds; 10,13,20,21 however, utilizing them is challenging because of limited sources, slow growth, and loss of function in vitro. In the case of liver, primary hepatocytes are mainly used to reseed decellularized liver scaffolds; 10,13,20,21 however, utilizing them is challenging because of limited sources, slow growth, and loss of function in vitro.…”
mentioning
confidence: 99%
“…Decellularized liver scaffold‐based engineering approach holds promises for developing functional liver surrogates . The resulting decellularized liver scaffold preserves a three‐dimensional (3D) matrix architecture that closely mimics the native liver and retains a plethora of matrix‐associated proteins as well as endogenous growth factors …”
Section: Introductionmentioning
confidence: 99%
“…A variety of cell types have been examined for liver scaffold recellularization, including immortalized cells, adult primary cells, fetal cells, mesenchymal stem cells and induced pluripotent stem cells . Many studies have shown that recellularized liver scaffolds perform hepatic specific functions in vitro .…”
Section: Introductionmentioning
confidence: 99%